2022
DOI: 10.3390/nu14122482
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness and Safety of Probiotics for Patients with Constipation-Predominant Irritable Bowel Syndrome: A Systematic Review and Meta-Analysis of 10 Randomized Controlled Trials

Abstract: To perform a systematic review and meta-analysis to evaluate the effectiveness and safety of probiotics in the treatment of constipation-predominant irritable bowel syndrome (IBS-C), we searched for randomized controlled trials (RCTs) comparing probiotic care versus placebos for patients with IBS-C in five comprehensive databases (March 2022). The risk of bias was assessed using the Cochrane Collaboration Risk of Bias Tool. RevMan 5.3 was used to perform a meta-analysis on stool consistency, abdominal pain, bl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(9 citation statements)
references
References 57 publications
0
9
0
Order By: Relevance
“…The included studies were notable for significant heterogeneity and confounding. A meta-analysis limited to constipation-predominant IBS found that probiotics improved stool consistency, but there were no significant differences in abdominal pain, bloating, or quality of life (52).…”
Section: Evidence For Prebiotics Probiotics and Synbiotics In Gi Cond...mentioning
confidence: 99%
“…The included studies were notable for significant heterogeneity and confounding. A meta-analysis limited to constipation-predominant IBS found that probiotics improved stool consistency, but there were no significant differences in abdominal pain, bloating, or quality of life (52).…”
Section: Evidence For Prebiotics Probiotics and Synbiotics In Gi Cond...mentioning
confidence: 99%
“…131 In addition, many patients with depression have IBS, which presents with chronic abdominal pain, diarrhea, and constipation of unknown cause (approximately 30% in the authors' cases above [Aizawa et al 132 ]). Since the efficacy of probiotics on IBS has been demonstrated by multiple meta-analytic studies, 135,136 for these cases, in particular, probiotics and fermented food containing beneficial microbes should be utilized and recommended.…”
Section: Probioticsmentioning
confidence: 99%
“…Details of many older trials that are not the focus of the current review can be found in that report. At least six systematic reviews have since been published on probiotics in IBS, examining the effects of probiotics at different levels of specificity [23 ▪ –28 ▪ ]; the considerable variation in reported effectiveness between different genera, species and strains is summarized in Table 1.…”
Section: Irritable Bowel Syndromementioning
confidence: 99%
“…However, aggregating the effects of different probiotics into a meta-analysis should be undertaken with caution as different probiotics have different characteristics that will inevitably impact on their efficacy. Indeed, network meta-analyses at genus and species levels showed differential effects across specific probiotics in IBS-C and IBS-D [24 ▪ ,27 ▪ ]. At a strain level, the effects were even more specific, with only four of six probiotics meta-analysed shown to be effective for improving global symptoms ( Bacillus coagulans MTCC5260, Bifidobacterium infantis 35624, two multistrain mixtures), and only four of 12 probiotics effective for reducing abdominal pain ( B. coagulans MTCC5260, Lactobacillus rhamnosus GG, two multistrain mixtures) [23 ▪ ].…”
Section: Irritable Bowel Syndromementioning
confidence: 99%